Human Herpesvirus 6A Infection-Associated Acute Anterior Uveitis - Ma H; Wang X; Chen Y; Zhang Y; Ren W; Sheng Y (Journal of Inflammation Research)
Huiling Ma,1 Xinyun Wang,1 Ying Chen,1 Yun Zhang,2 Weina Ren,3 Yan Sheng1 1Department of Ophthalmology, the First Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang Province, 310003, People’s Republic of China; 2Department of Retina Center, Affiliated Eye Hospital of Wenzhou Medical University, Hangzhou, Zhejiang Province, 310000, People’s Republic of China; 3Department of Ophthalmology, The Affiliated People’s Hospital of Ningbo University, The Eye Hospital of Wenzhou Medical University (Ningbo Branch), Ningbo, 315040, People’s Republic of ChinaCorrespondence: Yan Sheng, Department of Ophthalmology, the First Affiliated Hospital of Zhejiang University School of Medicine, Hangzhou, Zhejiang Province, 310003, People’s Republic of China, Email yansheng326@zju.edu.cnAbstract: Human herpesvirus 6 (HHV-6) infection can cause ophthalmic diseases in immunocompetent patients, recipients of bone marrow transplants, and patients with acquired immunodeficiency syndrome (AIDS). This study describes the case of a healthy 37-year-old male who presented with unilateral anterior uveitis (AU), significant anterior chamber exudation, pupillary membrane closure, increased intraocular pressure, and eyelid edema. Notably, HHV-6A was the only pathogenic agent identified in the blood and aqueous humor. The patient was treated with foscarnet sodium and ganciclovir, showing effective results. Additionally, based on the literature review, the hypothesized mechanism underlying HHV-6A-associated AU was discussed. To the best of our knowledge, this is the first case report of HHV-6A involvement in ocular inflammation and may provide a theoretical basis for further investigations of occurrences of HHV-6A-associated acute AU in clinical settings.Keywords: human herpesvirus 6A, acute anterior uveitis, secondary glaucoma